Preoperative Nutritional Scores as Host-Related Prognostic Factors for Both Overall Survival and Postoperative Complications in Patients With Stage II to III Colorectal Cancer. Issue 10 (26th April 2021) - Ahiko, Yuka; Shida, Dai; Nakamura, Yuya; Imaizumi, Jun; Takamizawa, Yasuyuki; Moritani, Konosuke; Tsukamoto, Shunsuke; Kanemitsu, Yukihide
Abstract : Supplemental Digital Content is available in the text. Abstract : BACKGROUND: In the TNM eighth edition, nutritional status and inflammatory scores are newly described as host-related prognostic factors for esophageal cancer, hepatocellular carcinoma, and pancreatic cancer. However, only age and race are listed as host-related prognostic factors for colorectal cancer. OBJECTIVE: The purpose of this study was to evaluate the prognostic significance of nutritional and inflammatory scores for postoperative outcomes in patients with colorectal cancer. DESIGN: This was a retrospective study using a database that prospectively collects data. SETTINGS: The study was conducted at a high-volume multidisciplinary tertiary cancer center in Japan. PATIENTS: Study participants were 1880 consecutive patients with stage II to III colorectal cancer who underwent curative resection at the National Cancer Center Hospital between 2004 and 2012. Two nutritional scores (prognostic nutritional index and controlling nutritional status score) and 4 inflammatory scores (modified Glasgow prognostic score, neutrophil:lymphocyte ratio, platelet:lymphocyte ratio, and C-reactive protein:albumin ratio) were calculated. MAIN OUTCOME MEASURES: Correlations of nutritional scores and inflammatory scores with overall survival and postoperative complications were measured. RESULTS: After adjusting for key clinical and pathologic factors by multivariable analysis, 2 nutritional scores (prognostic nutritional index and controlling nutritional status score) and 2 inflammatory scores (neutrophil:lymphocyte ratio and C-reactive protein:albumin ratio) were independent prognostic factors for overall survival. With respect to discriminative ability, time-dependent receiver operating characteristic curves and Harrell concordance index revealed that prognostic nutritional index and controlling nutritional status score were superior to the 4 inflammatory scores for predicting overall survival. Multivariable logistic regression analyses also revealed that prognostic nutritional index, controlling nutritional status score, and C-reactive protein:albumin ratio were independent predictors for postoperative complications. LIMITATIONS: The retrospective design of the study was a limitation. CONCLUSIONS: Preoperative nutritional scores are promising host-related prognostic factors for overall survival and postoperative complications in patients with stage II and III colorectal cancer. See Video Abstract at http://links.lww.com/DCR/B587 . EVALUACIÓN DE SCORE NUTRICIONALES PREOPERATORIOS COMO FACTORES PRONÓSTICOS PARA SOBREVIDA Y COMPLICACIONES POSTOPERATORIAS EN PACIENTES CON CANCER COLORECTAL ETAPA II Y III: ANTECEDENTES: En las últimas etapificaciones T-N-M, tanto el estado nutricional como inflamatorio han sido descritos como factores pronósticos en cáncer de esófago, hepático y pancreático. Sin embargo en cáncer colorectal solo la edad y la raza son enumerados como factores pronósticos. OBJETIVO: Evaluar la importancia pronóstica de los scores nutricionales e inflamatorias para los resultados posoperatorios en pacientes con cáncer colorrectal. DISEÑO: Estudio retrospectivo utilizando una base de datos. AJUSTE: Centro oncológico teciario en Japón. PACIENTES: Fueron incluidos en el estudio 1880 pacientes, consecutivos, con cancer colorectal etapa II y III sometidos a reseeción curativa en el National Cancer Center Hospital entre 2004 y 2012. Se aplicaron dos scores: nutricional (índice nutricional pronóstico y puntuación del estado nutricional) e inflamatorias (Glasgow modificada, proporción de neutrófilos a linfocitos, de plaquetas a linfocitos y de proteína C reactiva a albúmina). PRINCIPALES MEDIDAS DE RESULTADO: Evaluar scores nutricional e inflamatorio con sobrevida y complicaciones postoperatoria. RESULTADOS: Después de ajustar los factores clínicos y patológicos clave mediante análisis multivariable, dos scores nutricionales (índice nutricional pronóstico y puntuación del estado nutricional de control) y dos inflamatorias (proporción de neutrófilos a linfocitos y proporción de proteína C reactiva a albúmina) fueron pronósticos independientes factores para la sobrevida. Con respecto a la capacidad discriminativa, las curvas de características operativas del receptor, dependientes del tiempo y el índice de concordancia de Harrell, revelaron que el índice nutricional pronóstico y del estado nutricional de control eran superiores a las cuatro inflamatorias para predecir la sobrevida general. Los análisis de regresión logística multivariable también revelaron que el índice nutricional pronóstico, el estado nutricional de control y la relación proteína C reactiva / albúmina fueron predictores independientes de complicaciones postoperatorias. LIMITACIONES: Estudio de tipo retrospectivo. CONCLUSIONES: Los scores nutricionales preoperatorias son factores pronósticos prometedores relacionados con la sobrevida y las complicaciones postoperatorias en pacientes con cáncer colorrectal en estadio II y III. Consulte Video Resumen en http://links.lww.com/DCR/B587 .